A Study Of The Acceptance Of The Students Of Malaysian Private Higher Education Towards E-Learning - Chong, Fong Kim (2005)
This paper attempts to discuss Malaysian students' perception and readiness towards the E-Learning method. This paper also discusses the key factors that will influence the students to adopt E-Learning and the successful implementation of this new learning/teaching method to encourage life-long education in Malaysia.